Enacting Scenario Card-Lesson Study in Pre-service Teacher Education: A Case Study on Indonesian Pre-service Teachers with Disabilities - Luluk Sri Agus Prasetyoningsih; Prayitno Tri Laksono (AL-ISHLAH: Jurnal Pendidikan, 2021)
Pre-service teachers are agents involved in several teaching training before involving in the professional community. The present study was designed to look at the enactment of Scenario Card-Lesson Study (SCLS), a previously developed learning media. A single pre-service teacher with disabilities was voluntarily involved in the project. Data were garnered through multiple video-recorded observations and checklist documentation. Findings suggest that the participant demonstrated contextual practices of classroom teaching using SCLS. Based on the themed-finding, the participant designed the lesson plan effectively, improved classroom teaching skills, and wrote the lesson study report well. In addition, based on our observation session, The participant also engaged fully in student-student discussion and teacher-student interactions. One tangible finding from this study is that the participant appeared autonomous in designing the teaching and learning plans. Suggestions for policymakers, stakeholders, and future researchers in pre-service teacher education are offered in this paper.